2015
DOI: 10.3892/ol.2015.3817
|View full text |Cite
|
Sign up to set email alerts
|

Adult metastatic yolk sac tumor descending from an intra-abdominal testis: A case report and review of the literature

Abstract: Abstract. Pure yolk sac tumors are extremely rare in adults; to the best of our knowledge, <20 cases have been reported. Multiple metastases originating from a pure yolk sac testicular tumor, descending from an intra-abdominal testis, are additionally extremely rare. In the present case, a man exhibiting a 30-year history of cryptorchidism and indirect inguinal hernia, was admitted to the Department of Urology (The Second Xiangya Hospital, Changsha, China) due to a mass that had descended from the abdominal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Talerman et al did not found a single case of pure YST amongst 147 germ cell neoplasms of testis in adults which they observed over a 4½-year period [ 5 ]. Wang et al in their case report and literature review published in 2015 mentioned that less than 20 cases of pure yolk sac tumor in adults have been reported [ 3 ]. To the best of our efforts, we could find four more reported cases in literature published in English between 2015 and 2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Talerman et al did not found a single case of pure YST amongst 147 germ cell neoplasms of testis in adults which they observed over a 4½-year period [ 5 ]. Wang et al in their case report and literature review published in 2015 mentioned that less than 20 cases of pure yolk sac tumor in adults have been reported [ 3 ]. To the best of our efforts, we could find four more reported cases in literature published in English between 2015 and 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Pure YST of the testis in an adult is extremely rare [ 3 ]. In adults it exhibits a more aggressive behavior with a high frequency of metastasis compared to childhood YST [ 4 ].…”
Section: Introductionmentioning
confidence: 99%